Inter-ethnic and mono-ethnic families: examining the association of parenting and child emotional and behavioural adjustment - Tan, Jo Pei (Universiti Putra Malaysia Press, 2012)
Literature suggests that inter-ethnic children are not only one of the fastest growing populations in the last decade, but also show a higher prevalence of risk factor for poor outcomes, including family breakdown, academic underachievement and psychology maladjustment. The present research explores whether ethnicallymixed children are less well psychologically adjusted when compared to children from mono-ethnic families. Findings are reported from a study on the emotional and behavioural adjustments of children from 218 interethnic Malay-Chinese and 214 mono-ethnic Malay and Chinese families in Malaysia. The centrality of familial ethnicity status (inter vs. mono), parental relationships quality, and parenting behaviour were also explored as correlates of children’s psychological adjustment. Mother-child dyads were sampled for the survey and standardized self-administered questionnaires were utilised. In this sample of Malaysian families, multivariate analysis revealed that parental ethnicity mix, the quality of their marital relationships, and parenting behaviour predicted whether or not the children were emotionally and behaviourally adjusted. Overall, children from mixed parentage reported fewer emotional and behavioural problems than those from mono-ethnic minority families. The current study challenges traditional assumptions towards inter-ethnic families and shows that children of mixed-parentage may not be at risk of emotional and behavioural problems, as previously suggested. The findings have important implications for children development and interventions, with children of mixedparentage in today’s changing families.